Economic and Legal Principles of Cybersecurity as a Prerequisite for the Introduction of Special Economic Regimes - S.V. Sieriebriak (Аналітично-порівняльне правознавство, 2023)
The article conducts a scientific and practical study of the economic and legal aspects of the State policy in the field of cybercrime and its impact on business development in a particular region, country, etc. It is determined that the massive spread of cybercrime, the lack of effective mechanisms for combating economic crimes, and the leveling of conceptual approaches to creating an effective mechanism for legal support of the business environment development have a negative impact on the investment environment in particular and on ensuring sustainable development of the State as a whole. The author analyzes the regulatory and legal documents which form the legal basis of the mechanism for combating cybercrime, both at the international and national levels. The author identifies the weaknesses of the national system of legal regulation of cybersecurity. The author points out the sufficiency and fragmented nature of legislative support for cybersecurity and counteraction to the growth of economic crimes.